Task-based functional neuroimaging in infants: a systematic review - Agyeman, Kofi; McCarty, Tristan; Multani, Harpreet; Mattingly, Kamryn; Koziar, Katherine; Chu, Jason; Liu, Charles; Kokkoni, Elena; Christopoulos, Vassilios (Frontiers in Neuroscience, 2023)
 Practical and technical limitations, mainly associated with non-compliance, motion artifacts, and data acquisition are exacerbated in infant imaging. These constraints lead to high rates of participant exclusions and have resulted in a limited number of studies investigating motor systems in early infancy. Overcoming these challenges will require improvements to existing technology, or the development of a novel imaging technique that is age appropriate, portable, cost effective, and less susceptible to motion artifacts, while maintaining high spatiotemporal resolution.